Republic of Kazakhstan : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that Kazakhstan's economy continues to expand rapidly, with average real growth of more than 10 percent over the past three years, and an estimated 9.1 percent in the first quarter of 2004. Economic growth has been driven by increasing oil production, supported by high oil prices and rising foreign investments. Structural reforms are well advanced compared with other countries in the region, but the implementation of the reform agenda has slowed somewhat since 2000.